After shocks: The effects of internal sourcing on voluntary turnover. - Hardy, Jay H.; Thiel, Chase E.; Gibson, Carter; Klotz, Anthony C.; Barsa, Andrew (Journal of Applied Psychology, 2025)
difficult to retain in strong job markets (i.e., when job opportunities are plentiful relative to job seekers) because promotions increase an employee's external marketability. The onset of the COVID-19 pandemic-a global exogenous shock that triggered an event chain characterized by a weak job market followed by a historically strong one-provided a unique opportunity to test these competing perspectives. Drawing upon event system theory and the unfolding model of turnover, we argue that internal sourcing creates positive perceptions among employees about their employer, making them less inclined to seek external opportunities during periods of heightened employee mobility. Specifically, we predict that internally sourced employees perceive lower levels of employment threat and higher levels of organizational support than those hired externally, which mitigates their turnover risk in strong job markets. We tested these predictions in two studies: a longitudinal field study involving 11,072 restaurant managers who were newly promoted or hired into their roles in the years surrounding the onset of the COVID-19 pandemic and the strong job market that followed and an experiment designed to mirror the field study conditions, in which we examined the psychological mechanisms underlying this phenomenon. Collectively, the results of our studies support our predictions, offering valuable insights into the effects of internal versus external sourcing on employee retention. (PsycInfo Database Record (c) 2025 APA, all rights reserved).